What drives long-term oil market volatility? Fundamentals versus speculation - Libo Yin; Yimin Zhou (Economics: The Open-Access, Open-Assessment E-Journal, 2016)
This paper explores the role of speculation and economy fundamentals in the oil market using a two-component GARCH-MIDAS model. Specifically, the authors highlight the different roles played by the changing oil shocks with respect to the short-term and long-term components regarding oil market volatility. The results indicate that a global demand shock is the only factor found not only to be positive but to also significantly increase long- and short-term oil volatility in the full sample. This is consistent with a classic host of research that advocates that global demand dominates the oil market. However, since 2004, impacts of other oil shocks have been significantly weakened or even reversed. For example, the speculative demand shock has helped to stabilize long-term oil volatility during the post-2004 period. The results also suggest the existence of asymmetric impacts on short-term oil volatility, particularly for shocks from oil supply, oil-specific demand and oil speculative demand.
Keywords: Q43; 330; oil shocks; economy fundamentals; speculation; long/short-term oil volatility; GARCH-MIDAS model